Effectiveness of Yinhua Pinggan granules in community-acquired pneumonia: a randomized, double-blind clinical trial - Wang, Jiao-Li; Hu, Hao-Ran; Guo, Yi-Lei; Han, Jin; Wan, Hai-Tong; Tong, Yu-Xiao; Luo, Man; Li, Xian-Wen (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceCommunity-acquired pneumonia (CAP) is an acute inflammation of the alveoli and distal bronchi caused by bacterial, viral, or other pathogenic microbial infections. Yinhua Pinggan (YHPG) granules have demonstrated anti-inflammatory, antibacterial, and antiviral effects, suggesting their potential as a treatment option for CAP.AimTo assess the efficacy and safety of traditional Chinese medicine (TCM), YHPG granules, in combination with conventional pneumonia treatments.Materials and methodsThis randomized, double-blind, placebo-controlled clinical trial was conducted at a medical center in Hangzhou and involved 240 eligible participants. In addition to conventional pneumonia treatment, participants were randomly assigned in a 1:1 ratio to receive either YHPG granules or placebo for 10 days. The primary outcome measure was the difference in pneumonia cure rates at the end of treatment. Secondary outcomes included chest CT absorption rate, criticality score (SMART-COP score), Acute Physiology and Chronic Health Evaluation II (APACHE II) score, C-reactive protein (CRP) level, lactate (LC) level, procalcitonin (PCT) level, time for symptom recovery, length of hospital stay, and TCM syndrome scores.ResultsIn total, 229 participants were included in the analysis. The pneumonia cure rate in the YHPG granule group was higher than that in the placebo group (37.2% vs. 22.4%, mean difference: 14.75%, 95% CI: 3.05–26.46, p < 0.05), indicating the superiority of YHPG granules. The granules significantly improved the chest CT absorption rate, pneumonia severity, and CRP and LC levels (p < 0.05). Additionally, YHPG granules resulted in a shorter recovery time from fever and lung rales, reduced hospital stay, and lowered the TCM syndrome scores than the placebo (p < 0.05). No significant differences were observed in other outcomes between the two groups (p > 0.05). Notably, the use of YHPG granules was associated with fewer adverse reactions.ConclusionYHPG granules are a promising adjunct therapeutic agent for CAP.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=127908, identifier ChiCTR2100047501.